MINDFULNESS DAN PENERIMAAN DIRI PADA ANGGOTA KOMUNITAS JOGJA MINDFULNESS WEEKEND - Billy Tambunan; Berta Esti Ari Prasetya (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2022)
The mindfulness community is formed because it has special benefits for its members and one of them can be in the form of increasing self-acceptance for each individual who joins the group. This study aims to determine the relationship between mindfulness and self-acceptance among members of the Jogja Mindfulness Weekend community. The sampling method used was a saturated sampling technique involving 32 members of the Jogja Mindfulness Weekend community aged 20-50 years. Mindfulness data retrieval using the Five Facet Mindfulness Questionnaire (FFMQ) scale from Baer et al (2006) theory and has a Cronbach's alpha value = 0.896 while for self-acceptance using the Self-Acceptance Questionnaire (SAQ) scale from Sheerer theory (Sulistya, 2005) and has cronbach's alpha value = 0.942. Data retrieval via google form distributed to each participant with data analysis techniques using the Pearson product moment correlation test with the help of the SPSS ver 24 application. From the results of the study, the value of r = 0,767 (p<0,05) which means that there is a positive and significant relationship between mindfulness and self-acceptance. Thus Hypothesis (H1) is accepted where it shows that there is a positive and significant relationship between mindfulness and self-acceptance. This means, the higher the level of mindfulness, the higher the level of self-acceptance among members of the Jogja Mindfulness Weekend community. Vice versa, the lower the level of mindfulness, the lower the level of self-acceptance for members of the Jogja Mindfulness Weekend community.